Empowering Interactive Tools Based on IoT for Teaching ESP - Widiawati, Yogi; Ester, Eri; Danaryani, Sri (UICELE, 2026)
During pandemic of Covid19, both teachers and students are stressful because they have to do all activities through online. The teachers must work harder to prepare digital teaching aids to make students interested and then comprehend the material. The research is to find out which digital tools may help both English teachers and students, especially at Politeknik Negeri Jakarta (PNJ). in learning technical English vocabularies. As students of polytechnics, in certain semesters students must learn ESP (English for Specific Purposes). In practice, they find some obstacles in memorizing technical vocabularies which are very important in order to read and understand manual books for laboratory and workshop. During pandemic, most time of study are at home, so it is not easy for teachers to teach them. The modern teaching tools are using digital tools. The research made a kind of software which could be used for practicing their vocabulary memory as well as teaching them grammar, so they will be more skillful and knowledgeable. This software was made by using the program of Microcontroller ESP32. The software contains some exercises on reading text and reading comprehension questions and presented with the multiple answers. is handy and flexible which was flexible because students could bring it anywhere and be studied anytime. In other words, they have flexibility to learn and practice technical English vocabularies. The tool consists of 3 (three) sections of exercises. At the end of each exercise, the students are evaluated automatically by looking at the scoring system. These will motivate them to get good score. The most important thing is that by using this tool the students can practice technical English vocabulary and grammar both in classroom or at home.